√18×√1/2-√3/√12=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 00:31:38
√18×√1/2-√3/√12=√18×√1/2-√3/√12=√18×√1/2-√3/√12=
√18×√1/2-√3/√12=
√18×√1/2-√3/√12=
√18×√1/2-√3/√12=
√18×√1/2-√3/√12=
2/3√2-√1/2+√8-√3+√12-√18
计算:√4-√3/√12+√3-√2/√6+√2-√1/√2=?
√2+√8-√18=?3√3 -7√12 +4√27
计算:(√18-2√1/2- 3√1/3)-(√1/8-√12)=?
计算√12-√0.5-1/3+√18=
(√12-√4/3)-2(√1/8-1/√2-√18)
[√12-√(4/3)]-2[√(1/8)-1/√2-√18]
(√12-√0.5-2√1/3)-(√1/8-√18)
计算:①(√5-1)^2+(4/√5-1)②(√2+√3+√6)×(√2-√3+√6)③√27-(√1/3)=________④(√8又1/3)-(√3/8)-√54+(√1/3)=________⑤√3+√12-3√18+7√2⑥√48-1/3+√0.75⑦√75-(1/√3-√2)+
2√3+2-√3+1=_______3倍√8-5√2=__________√8+√1/3-2倍√1/2=_________√18-√8=______3√27-4√1/2+√8=_________(3√12-2√1/3+3倍√48)÷2√3=________
化简:√18-√8;(√3+1)²计算:(√2+1)(√2-1);√16+√0.25-³√27;√20+√5-2√5;√12+√48-3√1/3
√12-√0.5-√1/3+√18
√12+√0.5-√18+√(1/3)
(1)√18÷√2= (2)√18÷√8= (3)√12/2=(1)√18÷√2= (2)√18÷√8= (3)√12/2= (4)3/√6= (5)√2/3√40 = (6)√9/49=
(1)√12-√1/3=?(2)√8/2+2√18-1/4√32=?(3)√20×√5-8=?(4)(√8/27-5√6)×√6=?
√1/5=(),计算:√2/3-√3/2,√18-√8+√1/8,√25/2+√99-√18
((1/2)√3-2√12+3√18)÷2√(1/2)等于?